2017
DOI: 10.1002/art.40165
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Follicular Helper T Cell–Dependent B Cell Hyperactivity by Abatacept Treatment in Primary Sjögren's Syndrome

Abstract: Abatacept treatment in patients with primary SS reduces circulating Tfh cell numbers and expression of the activation marker ICOS on T cells. Lower numbers of activated circulating Tfh cells contribute to attenuated Tfh cell-dependent B cell hyperactivity and may underlie the efficacy of abatacept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 52 publications
9
110
1
Order By: Relevance
“…In addition, we observed that the frequencies of activated Tfh cells correlated with the clinical ESSDAI (ESSDAI without the biologic domain) scores , indicating that the correlation is not based only on activity in the biologic domain (e.g., hypergammaglobulinemia). A previous study by our group also supports an association between activated Tfh cells and disease activity. In that study, circulating Tfh cells in patients with primary SS were studied before and after treatment with abatacept .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In addition, we observed that the frequencies of activated Tfh cells correlated with the clinical ESSDAI (ESSDAI without the biologic domain) scores , indicating that the correlation is not based only on activity in the biologic domain (e.g., hypergammaglobulinemia). A previous study by our group also supports an association between activated Tfh cells and disease activity. In that study, circulating Tfh cells in patients with primary SS were studied before and after treatment with abatacept .…”
supporting
confidence: 82%
“…A previous study by our group also supports an association between activated Tfh cells and disease activity. In that study, circulating Tfh cells in patients with primary SS were studied before and after treatment with abatacept . In that study, we observed a significant decrease in the frequency of activated Tfh cells in blood during treatment.…”
supporting
confidence: 82%
“…Indeed, different murine models have demonstrated that CTLA-4 deletion led to autoimmune manifestations with increased Tfr cells (in both lymph nodes and blood). 162,[174][175][176] Overall, our findings suggest that immunopathogenic stratification of SS patients could be achieved through quantification of blood Tfh-and Tfr-cell subsets. 37,38 In humans, monogenic defects involving CTLA-4 and its intracellular trafficking regulator lead to a primary immunodeficiency characterized by recurrent infections and autoimmunity (characterized by inflammatory bowel disease, autoimmune endocrinopathies, and cytopenias).…”
Section: Tfr Cells For Clinical Precision Immunologymentioning
confidence: 65%
“…[155][156][157][158] However, a higher frequency of bTfr cells was found in patients with ankylosing spondylitis, systemic lupus erythematosus, and Sjögren's syndrome (SS). [159][160][161][162][163] Importantly, most of the literature describes studies where what is defined as Tfh cells contain both Tfh and CXCR5 + Tfr cells, likewise many other studies identify as Treg cells a mixture of conventional Treg cells together with Tfr cells. 15 An accurate assessment of the balance of Tfh to Tfr/ Treg populations requires quantification of the different subsets.…”
Section: Tfr Cells For Clinical Precision Immunologymentioning
confidence: 99%
“…The workflow described herein can be used for molecular profiling of RFs in patients with rheumatoid arthritis and other systemic autoimmune diseases, and readily adapted for targeted detection of other systemic autoantibodies. Furthermore, RF heavy‐chain molecular biomarkers hold promise for the monitoring of individual RF responses to conventional and biologic therapies for primary SS . Given that RF is an independent predictor of lymphoma in patients with primary SS , it will be interesting to sequence serum RFs to search for associations with particular Ig V H expression profiles and mutational patterns in patients progressing from initial presentation to MC and to lymphoma.…”
Section: Discussionmentioning
confidence: 99%